Heterogeneous zonal impacts of climate change on a wide hyperendemic area of human and animal fascioliasis assessed within a One Health action for prevention and control. - Pablo Fernando Cuervo; María Dolores Bargues; Patricio Artigas; Paola Buchon; Rene Angles; Santiago Mas-Coma (PLoS Neglected Tropical Diseases)
The Northern Bolivian Altiplano is the fascioliasis endemic area where the highest prevalences and intensities in humans have been recorded. In this hyperendemic area of human fascioliasis, the disease is caused only by Fasciola hepatica and transmitted by Galba truncatula, the sole lymnaeid species present in the area. When analysing the link between global warning and the recently reported geographical spread of lymnaeid populations to out-border localities, a marked heterogeneous climatic change was found throughout the endemic area. The aim of the present study was to analyse the physiographical heterogeneity of the fascioliasis hyperendemic area in the Northern Bolivian Altiplano, in order to assess its repercussions in the implementation of a One Health action. We applied multivariate linear mixed models to analyse the influence of a number of physiographical features on the long-term variation of climate and of the risk of transmission. Despite its apparent physiographic homogeneity, the findings of this study revealed markedly heterogeneous climate characteristics throughout the endemic area. This irregular pattern is influenced by physiographical features such as altitude, inner hills, closeness to Lake Titicaca, and El Niño-Southern Oscillation. This is the broadest study ever performed in a human fascioliasis endemic area about the influence of physiography on climate. It highlights the importance of considering physiographical features, an aspect usually not considered in studies dealing with the influences of climate and climate change on human and animal fascioliasis. Moreover, it shows that an endemic area may climatically evolve differently in its various inner zones and emphasizes the need for continuous monitoring to assess whether control measures should be modified accordingly.